Implementasi RFID SLiMS dan repositori digital di Perpustakaan Politeknik Negeri Bandung - Adika Subangkit; Davina Putri Ainny; Muhammad Rifqi Ibrahim (Universitas Pendidikan Indonesia, 2026)
The digitalization of academic libraries has become a strategic necessity to support the effectiveness of information services in higher education. This article aims to describe the implementation of student internships as a form of professional practice-based service in supporting the digitalization of services at the Bandung State Polytechnic Library. The discussion focuses on the implementation of Radio Frequency Identification (RFID) technology, optimization of the library automation system based on the Senayan Library Management System (SLiMS), and management of the institution's digital repository using the Ganesha Digital Library (GDL). The method used is a participatory approach and mentoring, where students are directly involved in the library's technical and operational activities. The results of the activities indicate that implementing RFID can improve the efficiency of circulation services and collection inventory, while optimizing SLiMS supports the integration of cataloging, circulation, and information access services through the OPAC. The management of digital repositories accompanied by document and metadata standardization contributes to improved access and retrieval of scientific works. The internship activities help strengthen human resources' readiness for the library's digital transformation. However, implementation remains limited to a portion of the collection and has not been accompanied by a quantitative evaluation of user satisfaction.